The Effectiveness of Youtube Channel @Menjadi Human in Providing Understanding of Mental Health for Communications Students of UIN North Sumatera (Pena Cendekia Insani, 2023)
Mental health is very important in human life because it is the main foundation that will determine how a person can accept and be accepted in his environment. This makes understanding mental health issues very important for every individual. In an effort to provide education on mental health issues, there is information about mental health that is packaged through narrative content on the YouTube channel